(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article is dedicated to analyzing the main aspects of tourism development in post-Soviet Kyrgyzstan. Significant attention is paid to studying the socio-economic and natural potential for the development of the republic’s tourism industry over the past 30 years. The necessity of accelerated integration of the Kyrgyz Republic into the global tourism space is asserted. The role of the private sector in the explosive progress of tourism under market conditions in the country is demonstrated. The most important elements of tourism infrastructure in the republic are analyzed. The main ways of modernizing the tourism industry in modern conditions are determined. Regional features of tourism development are briefly considered.